Analisis Higher Order Thinking Skills (HOTS) Siswa Sekolah Menengah Atas di Kota Pontianak - Erlin Eveline; Suparno Suparno (Sekolah Tinggi Keguruan dan Ilmu Pendidikan (STKIP) Melawi, 2021)
Abstract: The objective of this research was to measure higher-order thinking skills (HOTS) of Senior High School students in Pontianak. The steps in this study include: defining HOTS, determining the measured HOTS aspects and developing the HOTS test instrument, conducting research by giving HOTS questions to 272 senior high school students in Pontianak, and analyzing the students' HOTS as a whole and based on HOTS aspects. Data were analyzed using descriptive analysis techniques. The instrument of the test developed based on two HOTS aspects, namely: analyze and evaluate. The results showed that the percentage of HOTS class XI students in Pontianak for the categories